2017
DOI: 10.18544/pedm-23.02.0077
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status at the moment of diagnosis in childhood cancer patients

Abstract: ALL patients are less susceptible to underweight than the patients with the solid tumor. Moreover, the high incidence of overweight in children with ALL is noteworthy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…This is evident in studies like that of Maia Lemos et al [31] in Brazil, where undernourishment was found at diagnosis in up to 27.3% of patients, that of Villanueva et al [32] in Guatemala that reported 47% or that of Peccatori et al [33] in Nicaragua that reported 65.4%. The latter coincides with the undernourishment percentages reported in low and low to middle-income countries, where it reaches up to 40%-90% [34,35]. It is thereby important to emphasise that in the definition of malnutrition heterogeneity is a determinant of the variability reported in different studies, the methodology used to assess the nutritional status (anthropometric or biochemical measures) and the criteria or cut-off points that vary from population to population, thus making it difficult to accurately estimate the prevalence of cancer-related malnutrition [36].…”
Section: Discussionsupporting
confidence: 86%
“…This is evident in studies like that of Maia Lemos et al [31] in Brazil, where undernourishment was found at diagnosis in up to 27.3% of patients, that of Villanueva et al [32] in Guatemala that reported 47% or that of Peccatori et al [33] in Nicaragua that reported 65.4%. The latter coincides with the undernourishment percentages reported in low and low to middle-income countries, where it reaches up to 40%-90% [34,35]. It is thereby important to emphasise that in the definition of malnutrition heterogeneity is a determinant of the variability reported in different studies, the methodology used to assess the nutritional status (anthropometric or biochemical measures) and the criteria or cut-off points that vary from population to population, thus making it difficult to accurately estimate the prevalence of cancer-related malnutrition [36].…”
Section: Discussionsupporting
confidence: 86%
“…Similar results were obtained by Gurney et al and Pietila et al in clinical survivors of brain tumors who consider radiation therapy as the most important risk factor for obesity [17,18]. Our previous studies have shown that children with soft tissue tumors at the time of diagnosis are more prone to developing overweight and obesity compared to other types of childhood cancers [19]. There are several theories explaining the causes of such complications.…”
Section: Obesity/overweightsupporting
confidence: 86%
“…To our knowledge, this is the first prospective cohort study of the nutritional status of children with solid tumors in Brazil and the correlation with the outcomes. Few studies have addressed the nutritional assessment of pediatric patients with solid tumors 4,22,24,27 . In the present study, combination of the anthropometric indices, BMI/A z ‐score and MUAC percentile, to assess nutritional status highlighted the limitations of using BMI alone, especially in children with solid tumors who were undergoing treatment in an LMIC where large tumor masses are often present, which further limits the usefulness of the BMI/A for accurately assessing nutritional status.…”
Section: Discussionmentioning
confidence: 92%